=
Note: Conversion is based on the latest values and formulas.
From factorising a^2-b^2 hence or otherwise simplify fully (x^2 First the student should recognise that a 2-b 2 = (a-b)(a+b). Using this to solve (x 2 +4) 2-(x 2-2) 2 - Where a = (x 2 +4) and b = (x 2-2). Therefore substituting a and b into (a-b)(a+b)...(x 2 +4+x 2-2)(x 2 +4-x 2 +2) and simplifying...(2x 2 +2)(6). Expanding out the brackets gives: 12x 2 +12. Factorising out the 12 gives you 12(x 2 +1). The ...
The set of midpoints of the parallel chords of an ellipse ... - MyTutor => x 2 + 4( [mx] 2 + 2mxc + c 2) = 4. Rearranging: => {1 + 4m 2} x 2 + {8mc}x + (4c 2 - 4) = 0. This is a quadratic – the mean of the roots is when the there minimum is equal to zero. Differentiating and setting equal to zero: => 2{1 + 4m 2}x + 8mc = 0. Knowing this is satisfied for our chords to go through the midpoints, rearrange for the ...
Expand x(x+4) - MyTutor At what points does the line y = x +1 intersect the circle x^2 + y^2 + 18x + 20y + 81 = 0. Answered by Harry R. When given an equation with both letters and numbers on each side of the equals sign, for instance 4x +3 = 5x - 3, how do you know what to do first?
Given that y = 2^x, express 4^x in terms of y. - MyTutor Differentiate y = x^2 - 2x-3 + e^3x + 2ln(x) Answered by Jim H. When calculating a question with a double integral question between two different ranges which range relates to which integration variable.
(x+4)((x^2) - kx - 5) is expanded and simplified. The coefficient of ... The circle c has equation x^2+ y ^2=1 . The line l has gradient 3 and intercepts the y axis at the point (0, 1). c and l intersect at two points. Find the co-ordinates of these points.
The curve C has equation x^2 + 2xy + 3y^2 = 4. Find dy/dx. Here, we have to use implicit differentiation, along with the product rule. Remember that the product rule is (vu)' = vu'+uv'. Moving through the equation we have: x^2+2xy+3y^2 = 4 ==> 2x +2y + 2x*(dy/dx) + 6y*(dy/dx) = 0, remembering the rules of implicit differentiation. Factorising out dy/dx = -(2x+2y)/(2x+6y).
13 - 3 × 4+2 Simple question that lots of people get wrong 13 - 3 × 4 + 2 =13 - 12 + 2 (multiply first) ... y = 7:4 and x+y = 88 , work out the value of x–y ...
How do I factorise x^2 - 4? | MyTutor This is similar to other factorisation problems such as x 2 + 5x - 6. In this problem, you would find prime factors of -6 that add up to 5 (In this case -3, -2). Now, do the exact same with this problem! This is the same as x 2 + 0x - 4, so you need to find factors of -4 that add up to 0. In this case these two primes will be -2 and 2.
Find the minimum value of the quadratic equation: y = x^2 + 4x - 12 To complete the square of the above equation, halve the coefficient of x (number before x) to find the value of 'a' that goes inside the bracket - this is 4 divided by 2, which is 2. To find the letter 'b', take the constant from the end of the quadratic (in this case -12) and subtract the value of a 2 from it, so b = -12 - (2*2) = -12 - 4 = -16.
How do I know how many solutions a quadratic equation has? In the example above, we would have a = 1, b = 4 and c = -2. In order to find the number of solutions, we shall split the quadratic equation into 3 cases. Case 1: 2 unique solutions - eg x 2 + 5x + 6 = 0. Has solutions x = 2 and x = 3. Case 2: 1 repeated solution - eg x 2 + 4x + 4 = 0. Has solution x = 2. Case 3: No solutions - eg x 2 + 2x + 4 ...